PERUBAHAN MATA PENCARIAN DAN PENDAPATAN MASYARAKAT AKIBAT KONVERSI LAHAN PERTANIAN DI KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Yori, Riana; Dasrizal, Dasrizal; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
This study aimed to obtain information and data on changes mengganalisis livelihoods and incomes due to conversion of agricultural land in the District IV Jurai South Coastal District. The variables studied were changes in livelihoods and income levels due to land conversion pertanian.Metode research is descriptive. Population of this study was all the people who farm the conversion experience. Samples from the study area is residential area in District IV Jurai who experienced conversion in three areas, namely Lumpo, Kanagarian Salido, and Painan.Penarikan sample respondents was conducted with proporsinal Random Sampling technique by taking a sample of 54 respondents. Data was collected through questionnaires spread of the data was analyzed using descriptive analysis techniques with formula persentase.Hasil this study as follows: 1) conversion of land to bring change to changes in livelihoods that farmland conversion experience 2) conversion of land to bring changes to the income level of the community the conversion of farm experience.